Tumefactive demyelination: Clinical outcomes, lesion evolution and treatments. Issue 2 (June 2019) - Brod, Staley A; Lindsey, J William; Nelson, Flavia
Objective: Large demyelinating lesions with possible mass effect (tumefactive multiple sclerosis or tumefactive demyelination) can be mistaken for tumour-like space-occupying lesions suggesting a malignant outcome. Methods: We reviewed our own experience of multiple sclerosis subjects ( n  = 28) with tumefactive demyelination to determine the relationship between clinical outcomes and lesion evolution, clinical outcomes and their relationship to different therapies. Patients with central nervous system demyelinating disease were identified from our database over the last 10 years. Results: No patient increased in extended disability status scale (EDSS). Overall, lesion regression was associated with improved EDSS. Lesion regression was also associated with therapy versus no therapy. No specific therapy or corticosteroid infusions improved EDSS over the long term. The absence of enhancement on follow up on magnetic resonance imaging portended lesion regression. Conclusion: Tumefactive demyelination may predict a more benign overall course and is susceptible to traditional immunomodulatory treatments.